Determinants of Low Open Defecation Free (ODF) Status in the Implementation of the First Pillar of Community-Led Total Sanitation (CLTS) Program in Panjunan Village, Coastal Area of Cirebon City, Indonesia - Ramadhan, Nabilah Ulima Zafirah; Budiono, Irwan (Universitas Negeri Semarang, 2025)
Background: Open Defecation Free (ODF) is the first pillar of the Community-Led Total Sanitation (CLTS) program. The ODF achievement in Cirebon City is 82%. However, one area in Cirebon City, namely Panjunan Village, has an ODF achievement of only 70%. This study aims to analyze the causes of low ODF. Methods: This study used a qualitative approach with a case study design. Data collection was conducted in June-September 2024. The research subjects were residents of Panjunan Village, Cirebon City. Data were collected through six in-depth interviews and observations. Results: Based on the research results, there are several indicators that cause low ODF among the residents of Panjunan Village, including: Low literacy about CLTS, minimal support from cadres, as well as low awareness and community participation, in addition to limited sanitation facilities and infrastructure.